2004
DOI: 10.1039/b404827j
|View full text |Cite
|
Sign up to set email alerts
|

Efficient asymmetric hydrogenation with rhodium complexes of C1-symmetric 2,5-dimethylphospholane-diphenylphosphines

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim. . The crystal structure of 2a reveals that only one quadrant is blocked. Asymmetric hydrogenation of acrylic esters and enamides using 3a and 3b as catalysts show that the phenylene-backboned diphosphine gives a more efficient catalyst in terms of asymmetric induction than the more flexible ferrocene-backboned diphosphine.The be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 20 publications
1
28
0
Order By: Relevance
“…In the asymmetric hydrogenation of (Z)-N-benzoyl-1-phenylpropenamine the stereorecognition abilities of Rh-catalysts with UCAP-ligands especially those with bulkier aryl substituents on the achiral phosphorus center were superior to that observed with a related Rh-MeDuPHOS catalyst. A similar superiority of ligand 5a over Me-DuPHOS was noted in the Rh-catalyzed asymmetric hydrogenation of -amino acid precursors (up to 96 %ee) [81].…”
Section: Diarylphosphino Mono(phospholanes)mentioning
confidence: 83%
“…In the asymmetric hydrogenation of (Z)-N-benzoyl-1-phenylpropenamine the stereorecognition abilities of Rh-catalysts with UCAP-ligands especially those with bulkier aryl substituents on the achiral phosphorus center were superior to that observed with a related Rh-MeDuPHOS catalyst. A similar superiority of ligand 5a over Me-DuPHOS was noted in the Rh-catalyzed asymmetric hydrogenation of -amino acid precursors (up to 96 %ee) [81].…”
Section: Diarylphosphino Mono(phospholanes)mentioning
confidence: 83%
“…324,325 The ephedrine-based oxazaphospholidine-borane route has been applied to the synthesis of eight P-chiral monodentate ferrocenylphosphines of the general structure FcP(Ph)R, (R¼aryl or alkyl). 326 The reactivity of ferrocenylmethyl alcohols, esters, ethers and amines towards nucleophiles (often secondary phosphines) has been utilised in the synthesis of new phosphines, including a tridentate system, (140), combining planar-, P-and C-chirality, 327,328 bulky phosphines, e.g., (141) and (142), 329 a ferrocenylmethylphosphine-containing polymer, 330 rac-[2-(diphenylphosphino) ferrocenyl]acetic acid and related compounds, 331 and ferrocenylphosphines bearing imidazolium groups, precursors of phosphino-carbene ligands. 332,333 The same approach has been used in the synthesis of new P,N-ferrocenyl ligands, e.g., (143) 334 and (144).…”
Section: Miscellaneous Methods Of Preparing Phosphinesmentioning
confidence: 99%
“…An improved route to the simple secondary phospholane (71) has been developed, enabling the introduction of the chiral phospholane ring as a substituent in ferrocene and arenechromium complexes, e.g., (72). 140 The cyclic sulfate route has been applied in the synthesis of other ferrocenylphospholanes, e.g., (73) 141 and (74), 142 an ortho-phenylenebis(phospholane), 143 the bis(phospholanyl)maleic anhydride (75), 144 and a series of P-arylphospholanes bearing either chiral amine 145 or chiral dioxolanyl substituents in the ortho-position to phosphorus. 146 This route has also been used in the synthesis of sterically crowded phospholanes, e.g., (76 (75) Metallophosphide reagents have been applied widely in the synthesis of new chelating ligands involving two or more phosphorus atoms, and sometimes other additional donor centres.…”
mentioning
confidence: 99%
“…The ligand was purified via its dihydrochloride salt, liberating the free diphosphine quantitatively by treatment with NaHCO 3 . Independently, Saito [64] and Pringle [65] reported the use of 41 (R = Me, Ar = Ph) in Rh-catalyzed asymmetric hydrogenation of a range of olefins, with particularly good results being obtained for prochiral enamides. Saito and co-workers made a small family of this class of ligand, UCAPs, and demonstrated that adjusting the diaryl-substituted phosphine could lead to higher selectivities than Me-DuPhos for a trisubstituted enamide [64].…”
Section: Other Phospholane-containing Ligandsmentioning
confidence: 99%
“…Remarkably, large matching and mis-matching effects were observed for the Rh-catalyzed hydrogenation of MAC, with the (R,R,R) ligand giving complete conversion at 20 8C (96% ee), but the (S,R,R) ligand being inactive. Pringle also synthesized the ferrocenyl-based 43 [65], but showed this to be less efficient than the phenylene-linked analogue.…”
Section: Other Phospholane-containing Ligandsmentioning
confidence: 99%